Field notes contributed by Thomas J. Staudt, spring 1983 - Staudt, Thomas J.et al (1983)
Spring report of birds and locations contributed by Thomas J. Staudt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed